(untitled) - Brown, Raymond Edward; (1928-1998) (U.S.A, 1990)
The New Jerome Biblical Commentary is quite simply the best Catholic commentary available, to be used for studying the Scriptures. Aimed at anyone interested in religion and theology, lay or clergy, it is a single-volume containing verse-by-verse commentary on all the book of the Bible, complemented by topical articles. The articles present thoroughly up-to-date background information that is essential for full appreciation of the texts, at the same time offering the reader a wider perspective
Keywords: Bible -- Commentaries